Political Parties in the Pacific Islands - Hambly, Luke; G. Morgan, Michael; Rich, Roland (ANU Press, 2008)
While political parties remain an indispensable institutional framework for representation and governance in a democracy, the democracies of many Pacific Islands nations are undermined by the weakness and inefficacy of their local political parties. Addressing the implications of the lack of established party systems across the Pacific, this collection seeks to illuminate the underlying assumptions and suppositions behind the importance of coherent and effective parties to overall democratic functioning. Focusing on the political systems of East Timor, Papua New Guinea, Solomon Islands, Vanuatu, New Caledonia, Fiji and Samoa, the coherent structure of the volume makes it consistently useful as both an articulate analytical text and a reference tool concerning the political composition, history and direction of Pacific states. Featuring contributions from scholars who are familiar names to even the most casual of Pacificists, Political Parties in the Pacific is the benchmark reference work on the political parties of the Pacific: an invaluable resource for students, scholars and researchers of the Pacific and international politics.